Teknologi Informasi dan Komunikasi (TIK) dalam Membentuk Perilaku Peserta Didik - Perkasa, Gencar S (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
As the rapid growth of the Internet, advances in technology and globalization crashing into all aspects of life. Despite a late start, the development of the Internet in Indonesia is very promising. It spread quickly to the realm of national education. Various innovations were born and grown titled e-education such as e-learning, e-books, e-journals and so on. Support the learners in improving academic skills to meet the competition era of Information and Communication Technology (ICT) in the international arena. Various facilities always accompany the learning process. Changes in lifestyle and behavior of the students color the integration of the Internet into the government declared education through its curriculum in 2013. Behavioral changes learners make a new issue for education providers. Seiring berkembang pesatnya internet, kemajuan teknologi dan globalisasi menerjang ke segala lini kehidupan. Walaupun start terlambat, perkembangan internet di Indonesia sangat menjanjikan. Hal ini menjalar hingga ke ranah pendidikan nasional. Berbagai inovasi lahir dan berkembang bertajuk e-education seperti e-learning, e-book, e-journal dan sebagainya. Menunjang para peserta didik dalam meningkatkan kemampuan akademis menyongsong persaingan era Teknologi Informasi dan Komunikasi (TIK) di percaturan internasional. Berbagai kemudahan senantiasa mengiringi proses belajar mengajar. Perubahan gaya hidup dan perilaku peserta didik mewarnai pengintegrasian internet ke dalam pendidikan yang dicanangkan pemerintah melalui kurikulum 2013-nya. Perubahan tingkah laku peserta didik menjadikan persoalan baru bagi penyelenggara pendidikan.